Cell protection from Ca2+-overloading by bioactive molecules extracted from olive pomace. Issue 10 (19th May 2019) - Averna, Monica; Casazza, Alessandro A.; Martines, Antonino; Pedrazzi, Marco; Franchi, Alice; De Tullio, Roberta; Perego, Patrizia; Melloni, Edon
Abstract: We are reporting in the present study that molecules extracted from olive pomace prevent cell death induced by Ca 2+ -overloading in different cell types. Exposure of cells to these molecules counteracts the Ca 2+ -induced cell damages by reducing the activation of the Ca 2+ -dependent protease calpain, acting possibly through the modification of the permeability to Ca 2+ of the plasma membrane. The purification step by RP-HPLC suggests that effective compound(s), differing from the main biophenols known to be present in the olive pomace extract, could be responsible for this effect. Our observations suggest that bioactive molecules present in the olive pomace could be potential candidates for therapeutic applications in pathologies characterised by alterations of intracellular Ca 2+ homeostasis. Abstract :